Baseline Values and Kinetics of IL-6, Procalcitonin, and TNF-α in Landrace-Large White Swine Anesthetized with Propofol-Based Total Intravenous Anesthesia. (21st June 2021) - Chalkias, Athanasios; Spyropoulos, Vaios; Georgiou, Georgia; Laou, Eleni; Koutsovasilis, Anastasios; Pantazopoulos, Ioannis; Kolonia, Konstantina; Vrakas, Spyros; Papalois, Apostolos; Demeridou, Styliani; Gourgoulianis, Konstantinos; Dontas, Ismene; et al.
Abstract : The baseline levels of various inflammatory mediators and their changes during anesthesia in swine are not known. The aim of this animal study was to measure the baseline values and kinetics of interleukin-6, procalcitonin, and tumor necrosis factor-alpha in healthy Landrace-Large White swine anesthetized with propofol-based total intravenous anesthesia. We included 8 healthy male pigs with an average weight of 19 ± 2 kg (aged 10-15 weeks) that were subjected to propofol-based total intravenous anesthesia for 8 hours. Complete blood count, serum chemistry, and serum levels of interleukin-6, procalcitonin, and tumor necrosis factor-alpha were analyzed, and serum levels were quantified hourly. Blood was also collected for bacterial culturing. Baseline values of interleukin-6 and procalcitonin were 18 pg/ml and 21 ng/ml, respectively, while tumor necrosis factor-alpha was not detectable during collection of baseline samples. A statistically significant difference was observed in interleukin-6 levels between time points (p < 0.0001 ). Procalcitonin increased with time, but there were no significant differences between time points (p = 0.152 ). Tumor necrosis factor-alpha increased until the 3rd hour of propofol-based total intravenous anesthesia, while after the 4th hour, it gradually decreased, reaching its baseline undetectable values by the 7th hour (p < 0.001 ). Our results can serve as the basis for further translational research.